AN EMPIRICAL ANALYSIS OF FACULTY PERFORMANCE AND PERSPECTIVES IN JAPANESE BUSINESS SCHOOLS - Amaldas, Christine; Shankaranarayanan, Avinash; Gemba, Kiminori (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The research focuses on various factors influencing intrinsic and extrinsic motivational levels in international tenuredacademics and contractual teaching staff in Management and Business departments towards the adoption of Management of Technology (MOT) related methodologies. A set of hypotheses were defined to deduce the relationship between teaching and adoption of MOT as a framework. This research implies that job performance of international academics strongly depends on various motivational levels. The study was conducted using the interaction survey method with in-depth personal interviews consisting of open ended questions with 250 international academics (respondents consisting of Japanese and Foreign teaching staff) chosen for the study based in Japan. Hence, policy recommendationsand decision making should be dealt with prudence and pragmatism.